2021
DOI: 10.22161/ijaers.86.29
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Application of IoT and its Automation

Abstract: Life is getting more straightforward and easier to utilize as current technologies of automation continue to progress. Automatic systems are favored over manual ones in today's society. The internet has become an integral part of everyday life as its user base has grown tremendously over the past decade, and the Internet of Things (IoT) is the most current and rising internet technology. The Internet of Things is a rapidly expanding network of everyday objects, ranging from industrial robots to consumer gadget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Attackers can gather information, capture information, and transfer ownership of information to co-ops with expertise in the cloud thanks to information centralization. Because of this, widespread adoption of the cloud is being held back by worries about security, privacy, productivity, and flexibility [20][21][22]. In this attempt, we found that the handicraft arrangements' existing state only meets a portion of the requirements that are worrying us; a comprehensive arrangement that takes into account all the competing criteria is urgently needed [23][24][25][26].…”
Section: A Related Workmentioning
confidence: 99%
“…Attackers can gather information, capture information, and transfer ownership of information to co-ops with expertise in the cloud thanks to information centralization. Because of this, widespread adoption of the cloud is being held back by worries about security, privacy, productivity, and flexibility [20][21][22]. In this attempt, we found that the handicraft arrangements' existing state only meets a portion of the requirements that are worrying us; a comprehensive arrangement that takes into account all the competing criteria is urgently needed [23][24][25][26].…”
Section: A Related Workmentioning
confidence: 99%